Epochality, Global Capitalism and Ecology - Wayne Hope (tripleC: Communication, Capitalism & Critique)
What type of capitalism do we live in today? My answer to this question draws upon two interrelated lines of argument. Firstly, I will argue that we inhabit an epoch of global capitalism. The precursors of this kind of capitalism originated from the late nineteenth century when the development of telegraph networks, modern transport systems and world time zones provided a global template for industrialisation and Western imperialism. From about 1980 a confluence of global events and processes bought a fully-fledged global capitalism into being. These included the collapse of Fordist Keynesianism, national Keynesianism and Soviet Communism along with First, Second and Third World demarcations; the international proliferation of neo-liberal policy regimes; the growth of transnational corporations in all economic sectors; the predominance of financialisation and the reconstitution of global workforces. Secondly, I will argue that the shift from organic surface energy to underground fossil energy intertwined the time of the earth with the time of human history as nature was being instrumentalised as a resource for humanity. Understanding the capitalist relations of power involved here requires that we rethink the emergence of industrial capitalism in the historical context of a world system built upon unequal socio-ecological exchange between core and periphery. Today, global capitalism has intensified the anthropogenic feedback loops associated with CO2 emissions and climate change and universalised the organisational frameworks of profit extraction and socio-ecological destruction. I refer here to the transnational systems of fossil fuel capitalism along with their interlinkages with financialisation and advertising/commodity fetishism. From the preceding lines of argument I will briefly outline the intra-capitalist and planetary-ecological crises out of which transnational coalitions of opposition might emerge.